Species Diversity and Distribution of Artemia (Crustacea, Anostraca) in Iran: Historical Contexts and Updated Review - Asem, A.; Eimanifar, A.; Wink, M. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
In light of the pivotal role of Artemia Leach, 1819 as food in larviculture and fisheries, it becomes imperative to continually reassess its resources and deepen our understanding of its species diversity. Such efforts are essential for the effective management of its commercial exploitation and the promotion of sustainable aquaculture activities. Here we present a comprehensive review of historical documents dating back to the X century and contemporary scholarly articles. The findings indicate the existence of 59 sites (natural resources and farming sites) across Iran where Artemia has been recorded. This is a significant increase from the 23 reported in the last checklist in 2016. The data indicate that regional A. urmiana Günther, 1899 occurrences warrant classification as “Critically Endangered” on the “Regional Red List” of Iran. Remarkably, apparently the Bazangan Lake has a natural population of Artemia, probably a consequence of climatic change. We highlight the threat posed to Artemia species diversity by the invasive American brine shrimp A. franciscana Kellogg, 1906, noting its presence in 12 locations compared to 7 in 2016. Preliminary studies suggest that the indigenous parthenogenetic Artemia lineages in Iran exhibit superior production potential when compared to both A. franciscana and the native A. urmiana. In light of these findings, the study recommends prioritizing the utilization of native parthenogenetic Artemia in aquaculture, to conserve Artemia biodiversity.